Application of 5G Mobile Communication System to Artificial Intelligence: A Systematic Literature Review and Research Agenda - Irfan Mujahidin; Gisnaya Faridatul Avisyah (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2024)
The development and application of artificial intelligence is greatly influenced by the application of 5G mobile communication systems. In addition, applying 5G mobile communication systems in AI faces several challenges, such as the infrastructure to support 5G networks. By reviewing existing research and discovering issues and opportunities, this literature review aims to provide a comprehensive overview of recent advances in scalability and performance analysis of 5G networks for AI implementation. Research on 5G mobile communication systems has been conducted in health, environment, technology, and industry. The eight most commonly used methods in artificial intelligence research with 5G mobile communication systems are descriptive analysis, comparative studies, model development, case studies, regression models, literature studies, efficiency tests, and estimation techniques. However, the 5G mobile communication system in artificial intelligence technology still needs to be widely used, and its application in education still needs to be expanded. For some time, other researchers will be able to do this study.